Metabolic profiling of Buddleia indica leaves using LC/MS and evidence of their antioxidant and hepatoprotective activity using different in vitro and in vivo experimental models - Youssef, Fadia S.; Wink, Michael (Antioxidants, 2019)
LC-ESI-MS (Liquid Chromatography coupled with Electrospray Ionization Mass Spectrometry profiling of a methanol extract from Buddleia indica (BIM) leaves revealed 12 main peaks in which verbascoside and buddlenoid B represent the major compounds. The antioxidant and hepatoprotective activities of BIM were investigated using different in vitro and in vivo experimental models. BIM exhibited substantial in vitro antioxidant properties in DPPH· and HepG2 assays. Regarding CCl4 (carbon tetrachloride) induced hepatotoxicity in a rat model, oxidative stress markers became significantly ameliorated after oral administration of BIM. Lipid peroxide levels showed a 51.85% decline relative to CCl4-treated rats. Super oxide dismutase (SOD), total antioxidant status (TAS), and catalase (CAT) revealed a marked increase by 132.48%, 187.18%, and 114.94% relative to the CCl4 group. In a tamoxifen-induced hepatotoxicity model, BIM showed a considerable alleviation in liver stress markers manifested by a 46.06% and 40% decline in ALT (Alanine Transaminase) and AST (Aspartate Transaminase) respectively. Thiobarbituric acid reactive substances (TBARS) were reduced by 28.57% and the tumor necrosis factor alpha (TNF-α) level by 50%. A virtual screening of major secondary metabolites of BIM to TNF-alpha employing the C-docker protocol showed that gmelinoside H caused the most potent TNF- α inhibition as indicated from their high fitting scores. Thus, BIM exhibited a potent hepatoprotective activity owing to its richness in antioxidant metabolites.